Medicinal Plants Classification of Minangkabau and Mentawai; Structuralism Levi-Strauss Perspective - Arifin, Zainal; Delfi, Maskota; Priyambodo, Wahyu Joko (Jurnal Mamangan, 2018)
In 2012, research in medicinal plant species discovered around 297 different types in the Simanau and Maek villages of the Minangkabau region in West Sumatra, Indonesia. Sixty three of those were considered rare species, endangered with extinction. If it is studied deeply, it is possible that the types of medicinal plants in vilages of the Minangkabau region can amount to thousands of species. For this research, the structure of knowledge on practicing healer understood through ethnographic studies. This research result that the diversity and types of medicinal plants in Simanau village could be classified into four groups. This classification, known as ureh nan ampek, consisting of sitawa (antidote), sidingin (fresh taste), cikarau (defender) and cikumpai (destroyer). This suggests that the practicing healers have knowledge in recognizing the different types of plants that can be used for treatment, and have knowledge about how and what medicinal plants are used. This article attempts to understand the structure of knowledge of the practicing healers in Simanau village about the types and the classification of the medicinal plants.